PERKEMBANGAN POLITIK KETATANEGARAAN ISLAM DI INDONESIA - Hasanuddin Hasim (Fakultas Syariah Institut Agama Islam Negeri Palu, 2018)
The development of Islamic constitutional politics in Indonesia from time to time starting from the Dutch colonial period, the Japanese colonial period, the independence period, the old order period, the new order era and Islamic politics during the reformation era experienced different turmoil, not only in the form of structural reform government but to the grassroots of the community. Then over time, the scholars realized that their struggle would not succeed if they continued traditional methods. Therefore there needs to be a change which, although originating from its own colonial influence, is struggling through social education organizations or constitutional political movements. The presence of scholars in the political field should have a positive impact, contributing to the creation of a moral structure of political structures, because ulama are moral symbols. However, when the Ulama was polarized in such a way, that often between a cleric and other scholars faced each other and defended their respective parties. This condition will lead to division and the impact will confuse the people, so that it will weaken the strength of the Muslim community itself, which is often used by other party groups.